Patient-reported preferences for subcutaneous or intravenous administration of parenteral drug treatments in adults with immune disorders: a systematic review and meta-analysis - Vera Bril; Johannes Lampe; Nichola Cooper; Peter Kiessling; Ann Gardulf (Becaris Publishing Limited, 2024)
Aim: Several studies have found subcutaneous (SC) and intravenous (IV) administration of similar drugs for long-lasting immunological and autoimmune diseases to have similar clinical effectiveness, meaning that what patients report they prefer is, or should be, a major factor in treatment choices. Therefore, it is important to systematically compile evidence regarding patient preferences, treatment satisfaction and health-related quality of life (HRQL) using SC or IV administration of the same drug. Materials & methods: PubMed database searches were run on 15 October 2021. Studies involving patients with experience of both home-based SC and hospital-based IV administration of immunoglobulins or biological therapies for the treatment of any autoimmune disease or primary immunodeficiencies (PIDs) were included. The outcomes assessed were patient preferences, treatment satisfaction and HRQL. Preference data were meta-analyzed using a random-effects model. Results: In total, 3504 citations were screened, and 46 publications describing 37 studies were included in the review. There was a strong overall preference for SC over IV administration, with similar results seen for PIDs and autoimmune diseases: PID, 80% (95% confidence interval [CI], 64-94%) preferred SC; autoimmune diseases, 83% (95% CI: 73-92%); overall, 82% (95% CI: 75-89%). The meta-analysis also found that 84% (95% CI: 75-92%) of patients preferred administration at home to treatment in hospital. Analysis of treatment satisfaction using the life quality index found consistently better treatment interference and treatment setting scores with SC administration than with IV administration. Conclusion: Compared with IV infusions in hospital, patients tend to prefer, to be more satisfied with and to report better HRQL with SC administration of the same drug at home, primarily due to the greater convenience. This study contributes to evidence-based care of patients with autoimmune diseases or PIDs.